Wheel-Based MDM-PON System Incorporating OCDMA for Secure Network Resiliency - Meet Kumari; Vivek Arya; Hamza Mohammed Ridha Al-Khafaji (Photonics, 2023)
Wheel-based network resilience passive optical network (PON) based on mode division multiplexing (MDM) can be integrated with optical code division multiple access (OCDMA) schemes efficiently for the fixed and backhaul traffic under normal and break/failure fiber operating conditions. In this work, a bidirectional 10/2.5 Gbit/s hybrid MDM-OCDMA-PON system using multi-weight zero cross-correlation (MWZCC) code is proposed. Donut modes 0 and 1 are incorporated by the MDM technique in the proposed system. The benefit of this work is to offer an inexpensive, high-bandwidth and advanced long-haul network with satisfactory resource utilization ability for fiber links with protection against faults and to improve the reliability along with survivability of the network. The simulation results show the successful realization of the multimode fiber (MMF) link at 1.6 km in the uplink and 1.2 km in the downlink directions under an acceptable bit error rate (BER). The minimum accepted received power of −31 dBm in uplink and −27 dBm in downlink over 1 km link at 10/2.5 Gbit/s rate is obtained. Moreover, the minimum received power of −20 dBm in uplink and −30 dBm downlink is achieved by using MWZCC code compared to other codes handling 58 simultaneous end users. Further, the influence of fiber impairments and connected devices on the proposed approach is numerically evaluated. Moreover, it is shown that the wheel based proposed approach performs well than other topologies for the bidirectional network resilience transmission.